2009
DOI: 10.4314/wsa.v35i4.76808
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbial contamination at various sites along the Plankenburg- and Diep Rivers, Western Cape, South Africa

Abstract: This study was aimed at investigating and comparing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Most informal settlements are characterised by the lack of basic sanitation facilities and the inhabitants of such settlements mostly resort to rivers and nearby bushes as their main points of waste disposal. The impact of animal farming [33,34] and informal settlements on the microbial quality of aquatic ecosystems has been previously reported [4,35,36,37,38]. …”
Section: Resultsmentioning
confidence: 99%
“…Most informal settlements are characterised by the lack of basic sanitation facilities and the inhabitants of such settlements mostly resort to rivers and nearby bushes as their main points of waste disposal. The impact of animal farming [33,34] and informal settlements on the microbial quality of aquatic ecosystems has been previously reported [4,35,36,37,38]. …”
Section: Resultsmentioning
confidence: 99%
“…coli counts (p < 0.05) of up to 3.5 x 10 7 and 1.7 x 10 7 microorganisms/100 ml, respectively, for both river systems were obtained throughout the sampling period in the studies conducted by Paulse et al . [ 16 , 17 ]. Permission was not required from any authority or body to collect water at any of these locations.…”
Section: Methodsmentioning
confidence: 99%
“…The multiple tube fermentation technique as previously modified by Barnes [ 1 ] and employed by Paulse et al . [ 16 , 17 ], was used to enumerate fecal coliforms.…”
Section: Methodsmentioning
confidence: 99%
“…Various water quality studies have since been conducted in the estuary. Paulse et al (2009) investigated microbial contamination at three sites along the Diep River and found that, at all three sites, the microbial counts exceeded stipulated limits in terms of water quality guidelines. Jackson et al (2009), Hutchings and and Ayeni et al (2010) determined the extent of metal contamination along the lower Diep River.…”
Section: Water Qualitymentioning
confidence: 99%